Effects of pragmatic consciousness-raising activities on Iranian tertiary EFL learners’ performance and meta-pragmatic awareness in the speech act of suggesting - Abolfathiasl, Hossein (2014)
Learners of English as a foreign language appear to have problems with pragmatic features of the English language and often display a poor knowledge and performance in their communicative efforts. Although they may have developed a good knowledge of L2 grammar and vocabulary, EFL learners‟ ability to make pragmatically appropriate utterances in varying situations seems to lag behind. The significant role and spread of English as an international lingua franca for communication in a globalized world today makes this inability more noticeable and thus requiring more attention. Since EFL learners have limited or no opportunities to interact with native speakers to improve their pragmatic competence, providing them with effective instruction of the pragmatic features of English language has attracted much interest in recent years. To address the issue, the present study investigated the effects of pragmatic consciousness-raising (PCR) activities on Iranian intermediatelevel EFL learners‟ pragmatic performance and metapragmatic awareness of „suggestions‟. Fifty-two adult male learners in two intact classes, who were taking an intensive English language course at the Foreign language Center, Imam Ali University in Tehran, were assigned as an experimental group (n= 27) and a control group (n= 25). A pretest-posttest-delayed posttest design was used in the present study. The experimental group received PCR treatment for a period of 8 weeks. A written discourse completion test (WDCT) and a metapragmatic awareness test (MAT) were used to collect data during the study. The participants‟ pretest, posttest, and delayed posttest scores in both tests were analyzed to determine the effectiveness of the PCR treatment on the treatment group‟s production and metapragmatic awareness of suggestions. The result of repeated measures of ANOVA shows a statistically significant difference between the mean test scores in the pre-, post-, and delayed test measurements of participants‟ pragmatic performance in the experimental group, i.e. F(1.13, 29.39)= 393.4, p<.05. Moreover, the repeated measures of ANOVA for metapragmatic awareness revealed that the treatment group‟s mean scores in pre-, post-, and delayed testswere significantly different over time, i.e. F(2, 52)= 173.04, p<.05. Further, the independent samples t-test analysis of the delayed posttest scores of the treatment and control groups revealed that the difference between the mean scores of the two groups in the delayed WDCT is statistically significant, i.e. tobserved = 6.596> t-critical (50) = 2.008; α= .05. Finally, the independent samples ttest analysis of the delayed posttest scores of the treatment and control groups revealed that the difference between the mean scores of the two groups in the delayed MAT is statistically significant, i.e. t-observed = 4.25> t-critical (50) = 2.008; α= .05. Thus, the findings of the study provided evidence that PCR activities had a positive effect on Iranian EFL learners‟ pragmatic performance and metapragmatic awareness regarding the speech act of suggesting. In addition, the study showed that as a result of the PCR treatment, learners in the treatment group were able to use a wider range of structures and strategies as well as politeness strategies in making suggestions in their posttests performances. With regard to strategies, learners shifted from more direct strategies in the pretest to more indirect strategies and conventionalized forms in the posttests. Also, the number of learners who used a variety of politeness strategies in their post-treatment performances increased noticeably. The findings of the present study have implications for EFL teachers, teacher trainers, and material developers. However, more studies are needed to investigate the role and impact of pragmatic consciousness-raising approach in the EFL classroom further.